Quorum sensing employs a dual regulatory mechanism to repress T3SS gene expression - Payel Paul; Ram Podicheti; Logan J. Geyman; Elizabeth N. Baker; Kai Papenfort; Douglas B. Rusch; Julia C. van Kessel (mBio)
ABSTRACT The type III secretion system (T3SS) is a needle-like complex used by numerous bacterial pathogens in host infection to inject exotoxins into the host cell cytoplasm. The T3SS is a known virulence factor in the shrimp pathogen Vibrio campbellii. The ~40 genes comprising the V. campbellii T3SS are regulated by a network of transcription factors in response to changes in the cell’s environment: cell density (quorum sensing; QS), temperature, calcium, and host cell contact. Under positive environmental stimuli, the master T3SS transcription factor ExsA activates the expression of the four structural T3SS operons required for needle formation. Previous studies identified a key role of the master QS transcription factor LuxR: repression of exsA transcription via DNA binding at the exsBA promoter. Here, we uncovered a new regulatory role of LuxR: post-translational repression of ExsA activity via transcriptional repression of the gene encoding the anti-anti-activator ExsC. In V. campbellii, ExsC is a positive regulator of T3SS transcription; deletion of exsC decreases ExsA-dependent transcription activation of the T3SS structural promoters. Through genetic epistasis and in vitro biochemical assays, we show that LuxR directly binds the exsC promoter upstream of ExsA and represses transcription of exsC. Our findings collectively show that V. campbellii responds to high cell density signals to shut down ExsA-dependent expression of the T3SS via two mechanisms. We postulate that this dual regulatory mechanism by LuxR enables both the rapid inactivation of existing ExsA protein and blocks its further synthesis, leading to a rapid shutdown of T3SS activity at high cell density.IMPORTANCEVibrio campbellii utilizes the type III secretion system (T3SS) as a mechanism of pathogenesis, which is a highly studied “injectisome” complex that delivers exotoxins into host cells during infection. The T3SS pathogenicity island in V. campbellii comprises ~40 genes that are organized into four structural operons. In this study, we determined that quorum sensing—a method of bacterial communication—regulates T3SS genes both at the transcriptional and post-translational levels to shut down T3SS gene expression at high population densities.